Letter (copy) : Ricardo Zabalza - Citrine, Walter, 1887-1983
013-0119-001 International. WMC/WJB/DT/426. 4th January 1940. Mr. W. Carrillo, Bayswater Hotel, Bayswater Road, LONDON. W.2. Dear Mr. Carrillo, RICARDO ZABALZA. I duly received your letter of the 30th ultimo from which I was very sorry to hear of the serious position in which Ricardo Zabalza, former Secretary of the Land Workers' Union has been placed. I may say that I received similar news from another source. I immediately took the matter up with the Authorities and earnestly requested them to consider what steps could be taken to prevent the sentence passed on Zabalza from being carried out, and to alleviate the position of the other trade union leaders and socialists in Spain. Yours faithfully, General Secretary 292/946/13/119